2D / 3D Coupled S-Type Heterojunction SnS2 / ZnSn(OH)6 Photocatalyst and Its Application
Patent Information
- Application Number
- CN202611085710.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-20
Smart Images

Figure REF-OBJ-1784624230419-000001 
Figure REF-OBJ-1784624230419-000002 
Figure REF-OBJ-1784624230419-000003
Abstract
Description
Technical Field
[0001] This invention belongs to the fields of environmental functional photocatalytic materials technology and air pollution control technology, specifically relating to a 2D / 3D coupled S-type heterojunction SnS2 / ZnSn(OH)6 photocatalyst and its preparation method, a supported monolithic photocatalytic material and its application in nitrogen oxide purification. Background Technology
[0002] Nitrogen oxides (NOx) are among the major air pollutants and are important precursors to photochemical smog, acid rain, and fine particulate matter (PM2.5), posing a serious threat to the atmospheric environment and human health. Currently, NOx removal methods mainly include selective catalytic reduction (SCR), selective non-catalytic reduction (SNCR), biofiltration, and wet scrubbing. However, these traditional methods are not suitable for removing low concentrations of NOx in the atmosphere. Among these, SCR / SNCR denitrification technologies suffer from high operating costs, susceptibility of catalysts to heavy metal contamination, and secondary pollution due to ammonia escape, making them unsuitable for treating low-concentration, unsteady-state NOx. Compared to the aforementioned technologies, semiconductor photocatalysis technology has attracted widespread attention because it can utilize renewable and clean solar energy to achieve deep mineralization of pollutants under green and mild conditions.
[0003] Zinc hydroxystannate (ZnSn(OH)6), as a novel wide-bandgap semiconductor photocatalyst with ultraviolet light response, has been widely used in energy conversion, air purification, and wastewater treatment. ZnSn(OH)6 possesses advantages such as being economical, safe, non-toxic, and exhibiting excellent photoelectric properties. However, its large bandgap, narrow spectral response range, high photogenerated carrier recombination rate, and low utilization rate severely hinder its practical application. Single-component ZnSn(OH)6 exhibits extremely low visible light utilization and very poor photocatalytic activity.
[0004] Tin disulfide (SnS2), as a typical two-dimensional layered metal sulfide semiconductor material, possesses a narrow band gap and good visible light response. However, pure SnS2 nanosheets suffer from high photogenerated charge recombination rates and poor structural stability, thus limiting the photocatalytic activity of a single component.
[0005] To address the shortcomings of the existing technologies, there is an urgent need to develop a composite photocatalyst and its preparation method that can achieve complementary advantages between two-dimensional SnS2 and three-dimensional ZnSn(OH)6 structures, close interfacial contact, scalable preparation, and meet the requirements of engineering applications. Summary of the Invention
[0006] To address the limitations of existing traditional denitrification technologies, the low activity of single-component photocatalysts, the loose interfacial contact of conventional heterojunctions, the difficulty in achieving complementary structural advantages of materials with different dimensions, and the difficulty in engineering applications of powder catalysts, this invention provides a 2D / 3D coupled S-type heterojunction SnS2 / ZnSn(OH)6 photocatalyst and its preparation method.
[0007] This invention utilizes an in-situ growth strategy to grow two-dimensional SnS2 nanosheets on the surface of a three-dimensional ZnSn(OH)6 polyhedron, thereby constructing a 2D / 3D composite structure with close interfacial contact and achieving complementary advantages of two-dimensional and three-dimensional materials in terms of structure and function.
[0008] Meanwhile, this invention provides an alumina foam ceramic supported molding process, which solves the problem of easy loss of powder catalysts and difficulty in practical application, and provides a new type of high-performance, engineerable photocatalytic material and preparation scheme for the treatment of low-concentration NOx pollution in the atmosphere.
[0009] To achieve the above objectives, the present invention adopts the following technical solution: This invention discloses a 2D / 3D coupled S-type heterojunction SnS2 / ZnSn(OH)6 photocatalyst, wherein the SnS2 / ZnSn(OH)6 photocatalyst comprises a three-dimensional polyhedral ZnSn(OH)6 substrate and two-dimensional SnS2 nanosheets, wherein the two-dimensional SnS2 nanosheets are grown in situ on the surface of the three-dimensional polyhedral ZnSn(OH)6 substrate to form a two-dimensional / three-dimensional composite structure.
[0010] As a preferred technical solution, in the SnS2 / ZnSn(OH)6 photocatalyst, the molar ratio of SnS2 to ZnSn(OH)6 is 1:1 to 5:1.
[0011] As a preferred technical solution, in the SnS2 / ZnSn(OH)6 photocatalyst, the molar ratio of SnS2 to ZnSn(OH)6 is 3:1.
[0012] This invention discloses a method for preparing the above-mentioned SnS2 / ZnSn(OH)6 photocatalyst, comprising the following steps: (1) Preparation of three-dimensional polyhedral ZnSn(OH)6 powder; (2) Disperse the ZnSn(OH)6 powder obtained in step (1) in a solvent, add a sulfur source, and carry out a solvothermal reaction; (3) After the reaction is completed, cool, separate, wash and dry to obtain SnS2 / ZnSn(OH)6 composite powder.
[0013] As a preferred technical solution, the preparation of three-dimensional polyhedral ZnSn(OH)6 powder in step (1) includes: (1a) Dissolve zinc salt and citric acid in deionized water to prepare solution A, and disperse tin salt in anhydrous ethanol to prepare solution B; (1b) Mix solution A and solution B, and add alkali solution to carry out the reaction; (1c) Add alkali solution to the system obtained in step (1b); (1d) Collect the precipitate, wash and dry it to obtain three-dimensional polyhedral ZnSn(OH)6 powder.
[0014] As a preferred technical solution, the zinc salt is zinc chloride, the tin salt is tin tetrachloride pentahydrate, and the citric acid is citric acid monohydrate; the alkaline solution in steps (1b) and (1c) is sodium hydroxide solution.
[0015] As a preferred technical solution, in step (2), the sulfur source is thioacetamide, the solvothermal reaction temperature is 180-220℃, and the reaction time is 10-14h.
[0016] The present invention also discloses a supported monolithic photocatalytic material comprising the SnS2 / ZnSn(OH)6 photocatalyst and a porous support, wherein the SnS2 / ZnSn(OH)6 photocatalyst is supported on the surface of the porous support.
[0017] As a preferred technical solution, the porous carrier is alumina foam ceramic, glass fiber mesh, activated carbon, or honeycomb ceramic.
[0018] The present invention also discloses the application of the SnS2 / ZnSn(OH)6 photocatalyst or the supported monolithic photocatalytic material in the photocatalytic degradation of nitrogen oxides.
[0019] The beneficial effects of this invention are as follows: (1) This invention is the first to anchor two-dimensional SnS2 nanosheets onto the surface of a three-dimensional ZnSn(OH)6 polyhedron through an in-situ growth strategy, breaking through the limitations of composite materials of the same dimension and realizing the complementary advantages of two-dimensional / three-dimensional materials in terms of structure. The two-dimensional SnS2 nanosheets provide fast electron transport channels and broadband light-harvesting capabilities, while the three-dimensional ZnSn(OH)6 polyhedron provides a stable supporting framework, abundant reaction sites, and multi-dimensional mass transfer channels.
[0020] (2) The present invention uses a self-template method to prepare three-dimensional ZnSn(OH)6 and an in-situ solvothermal method to grow SnS2. The two-step process is simple and controllable, with mild conditions, no need for noble metal doping, and easy to prepare on a large scale and promote industrialization.
[0021] (3) This invention can directionally regulate the interfacial microstructure and composite material properties by precisely controlling the molar ratio of sulfur source to ZnSn(OH)6 (1:1 to 5:1), with 3:1 being the optimal ratio. The control of the amount of sulfur source directly affects the growth density, grain size and interfacial contact state of SnS2 on the ZnSn(OH)6 surface, providing a simple and effective control method for performance optimization.
[0022] (4) The SnS2 / ZnSn(OH)6 composite photocatalyst of the present invention significantly improves the NO photocatalytic removal efficiency, which is 15.3 times that of pure SnS2 and 99.2 times that of pure ZnSn(OH)6, respectively, solving the problem of extremely low activity of traditional single-component photocatalysts.
[0023] (5) The present invention is equipped with a PTFE-assisted alumina foam ceramic loading process to make the powder catalyst into an integral catalytic module, which effectively avoids the problems of powder loss and agglomeration, and can be directly adapted to the engineering application requirements of fixed working conditions such as air purification and industrial exhaust gas denitrification. The catalyst structure after loading and molding is stable and not easy to fall off, and can retain excellent photocatalytic activity.
[0024] (6) The raw materials used in this invention are inexpensive and readily available (citric acid monohydrate, sodium hydroxide, zinc chloride, tin tetrachloride pentahydrate, thioacetamide, and anhydrous ethanol are all commonly used industrial / analytical grade reagents), and the preparation process has no toxic byproduct emissions. It is green, environmentally friendly, and low in cost, and has extremely high industrial promotion value.
[0025] (7) This invention clarifies the regulatory effect of 2D / 3D interface contact and in-situ growth strategy on the structure and properties of composite materials, and provides a general strategy that can be referenced for the design and preparation of similar multidimensional heterojunction photocatalytic materials. Attached Figure Description
[0026] To make the objectives, technical solutions, and beneficial effects of this invention clearer, the following figures are provided for illustration: Figure 1 The image shows the XRD pattern of the ZnSn(OH)6 catalyst.
[0027] Figure 2 SEM image of ZnSn(OH)6 catalyst.
[0028] Figure 3 This is a TEM image of the ZnSn(OH)6 catalyst.
[0029] Figure 4 SEM image of the SnS2 / ZnSn(OH)6 composite catalyst.
[0030] Figure 5 TEM image of the SnS2 / ZnSn(OH)6 composite catalyst.
[0031] Figure 6 The EDX elemental distribution diagram of the SnS2 / ZnSn(OH)6 composite catalyst.
[0032] Figure 7 The XRD pattern of the SnS2 / ZnSn(OH)6 composite catalyst is shown.
[0033] Figure 8 XPS spectra of SnS2, ZnSn(OH)6 and SnS2 / ZnSn(OH)6 composite catalysts.
[0034] Figure 9 Photocurrent response diagrams for SnS2, ZnSn(OH)6 and SnS2 / ZnSn(OH)6 composite catalysts.
[0035] Figure 10 This is a comparison chart of the NO removal efficiency of different catalysts.
[0036] Figure 11 The activity cycle diagram of the photocatalytic degradation of NO by the SnS2 / ZnSn(OH)6 composite catalyst is shown.
[0037] Figure 12 This is a long-term reaction activity diagram of the photocatalytic degradation of NO by the SnS2 / ZnSn(OH)6 composite catalyst supported on foam ceramic. Detailed Implementation
[0038] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.
[0039] Example 1: Preparation of a three-dimensional ZnSn(OH)6 polyhedron Dissolve 1.26 g of citric acid monohydrate and 0.816 g of zinc chloride in 60 mL of deionized water and stir magnetically until completely dissolved to prepare solution A; disperse 2.1 g of tin tetrachloride pentahydrate in 30 mL of anhydrous ethanol and stir magnetically until completely dissolved to prepare solution B. Mix solution A and solution B, then add 2.448 g NaOH and 150 mL deionized water sequentially, and stir magnetically for 15 min; then add 120 mL of alkaline solution containing 9.6 g NaOH dropwise, and continue stirring magnetically for 15 min to complete the etching process; After the reaction was completed, the precipitate was collected by centrifugation and washed three times alternately with anhydrous ethanol and deionized water. The washed precipitate was then dried overnight in an oven at 60 °C to obtain white ZnSn(OH)6 powder.
[0040] Example 2: Preparation of SnS2 / ZnSn(OH)6 composite photocatalyst (SnS2 to ZSH molar ratio 1:1) Take 0.5 g of ZnSn(OH)6 powder prepared in Example 1, add a certain amount of thioacetamide, and calculate that the molar ratio of SnS2 to ZnSn(OH)6 is 1:1; add 60 mL of anhydrous ethanol and stir magnetically for 30 min to disperse evenly. The above mixture was transferred into a polytetrafluoroethylene hydrothermal reactor and reacted in an oven at 200 °C for 12 h. After naturally cooling to room temperature, the precipitate was separated by centrifugation and washed three times each with deionized water and anhydrous ethanol. The washed product was dried overnight in an oven at 60 °C to obtain SnS2 / ZnSn(OH)6 composite powder.
[0041] Example 3: Preparation of SnS2 / ZnSn(OH)6 composite photocatalyst (SnS2 to ZSH molar ratio 3:1) Take 0.5 g of ZnSn(OH)6 powder prepared in Example 1, add a certain amount of thioacetamide, and calculate that the molar ratio of SnS2 to ZnSn(OH)6 is 3:1; add 60 mL of anhydrous ethanol and stir magnetically for 30 min to disperse evenly. The above mixture was transferred into a polytetrafluoroethylene hydrothermal reactor and reacted in an oven at 200 °C for 12 h. After naturally cooling to room temperature, the precipitate was separated by centrifugation and washed three times each with deionized water and anhydrous ethanol. The washed product was dried overnight in an oven at 60 °C to obtain SnS2 / ZnSn(OH)6 composite powder.
[0042] Example 4: Preparation of SnS2 / ZnSn(OH)6 composite photocatalyst (SnS2 to ZSH molar ratio 5:1) Take 0.5 g of ZnSn(OH)6 powder prepared in Example 1, add a certain amount of thioacetamide, and calculate that the molar ratio of SnS2 to ZnSn(OH)6 is 5:1; add 60 mL of anhydrous ethanol and stir magnetically for 30 min to disperse evenly. The above mixture was transferred into a polytetrafluoroethylene hydrothermal reactor and reacted in an oven at 200 °C for 12 h. After naturally cooling to room temperature, the precipitate was separated by centrifugation and washed three times each with deionized water and anhydrous ethanol. The washed product was dried overnight in an oven at 60 °C to obtain SnS2 / ZnSn(OH)6 composite powder.
[0043] Example 5: Preparation of Supported Monolithic Photocatalytic Materials Take 1.5 g of the SnS2 / ZnSn(OH)6 composite powder prepared in Example 3, mix it with 40 mL of anhydrous ethanol, add 5 μL of PTFE emulsion, and ultrasonically disperse for 10 min to form a stable suspension.
[0044] The above suspension was slowly dripped onto the surface of an alumina foam ceramic substrate with dimensions of 10×10×2.2 cm, ensuring that the suspension uniformly covered the substrate surface.
[0045] The loaded foam ceramic was dried in a 60 ℃ oven for 12 h to obtain the supported monolithic photocatalytic material SnS2 / ZnSn(OH)6-FC.
[0046] Comparative Example 1: Preparation of pure ZnSn(OH)6 photocatalyst Three-dimensional ZnSn(OH)6 polyhedral powder was prepared according to the method in Example 1, without subsequent SnS2 in-situ growth treatment, and served as a control sample.
[0047] Comparative Example 2: Preparation of pure SnS2 photocatalyst 0.701 g of tin tetrachloride pentahydrate and 0.301 g of thioacetamide were dissolved in 60 mL of anhydrous ethanol and magnetically stirred for 30 min. The mixture was then transferred to a polytetrafluoroethylene hydrothermal reactor and kept at 200 °C for 12 h. After natural cooling, the precipitate was separated by centrifugation, washed with deionized water and anhydrous ethanol, and dried at 60 °C overnight to obtain pure SnS2 powder, which was used as a control sample.
[0048] Performance Tests and Results (1) Crystal structure characterization The ZnSn(OH)6 powder prepared in Example 1 was characterized by XRD, and the results are as follows: Figure 1 As shown, the positions of the diffraction peaks are consistent with those of the ZnSn(OH)6 standard card (JCPDS No. 20-1455), indicating that pure phase ZnSn(OH)6 was successfully prepared.
[0049] The SnS2 / ZnSn(OH)6 composite powder prepared in Example 3 was characterized by XRD, and the results are as follows: Figure 7 As shown, the XRD pattern of the composite material shows characteristic diffraction peaks of both ZnSn(OH)6 and SnS2, and no other impurity phases were detected, indicating that the SnS2 / ZnSn(OH)6 composite material was successfully prepared.
[0050] (2) Microscopic morphological characterization The ZnSn(OH)6 powder prepared in Example 1 was characterized by SEM and TEM, and the results are as follows: Figure 2 and Figure 3As shown, ZnSn(OH)6 exhibits a regular three-dimensional polyhedral morphology with a smooth surface and uniform size.
[0051] The SnS2 / ZnSn(OH)6 composite powder prepared in Example 3 was characterized by SEM and TEM, and the results are as follows: Figure 4 and Figure 5 As shown, two-dimensional SnS2 nanosheets are uniformly grown in situ on the surface of a three-dimensional ZnSn(OH)6 polyhedron, forming a tight interfacial contact between them, and no obvious aggregation or separation was observed.
[0052] EDX elemental distribution analysis was performed on the SnS2 / ZnSn(OH)6 composite powder prepared in Example 3, and the results are as follows: Figure 6 As shown, Sn, Zn, O, and S elements are uniformly distributed in the composite material, further confirming the uniform growth of SnS2 on the ZnSn(OH)6 surface.
[0053] (3) Characterization of surface chemical state XPS characterization was performed on pure SnS2, pure ZnSn(OH)6, and the SnS2 / ZnSn(OH)6 composite powder prepared in Example 3. The results are as follows: Figure 8 As shown, the characteristic element binding energies of the composite material shifted compared to the pure components, indicating an interfacial electronic interaction between SnS2 and ZnSn(OH)6.
[0054] (4) Photoelectric performance characterization The photocurrent response of pure SnS2, pure ZnSn(OH)6, and the SnS2 / ZnSn(OH)6 composite powder prepared in Example 3 was tested, and the results are as follows: Figure 9 As shown, the photocurrent density of the composite photocatalyst is significantly higher than that of the single component, indicating that the 2D / 3D composite structure effectively promotes the separation and transport of photogenerated charges.
[0055] (5) Photocatalytic NO removal performance test Under visible light irradiation, the NO photocatalytic removal efficiency of pure ZnSn(OH)6 (Comparative Example 1), pure SnS2 (Comparative Example 2), and the SnS2 / ZnSn(OH)6 composite powder prepared in Examples 2-4 were tested respectively. The results are as follows: Figure 10 As shown.
[0056] Pure ZnSn(OH)6 exhibits extremely low NO removal efficiency, while pure SnS2 shows limited NO removal efficiency. The SnS2 / ZnSn(OH)6 composite photocatalysts prepared in Examples 2-4 all demonstrated significantly higher NO removal efficiencies than their single-component counterparts. Among them, Example 3 (SnS2 to ZSH molar ratio 3:1) showed the highest NO removal efficiency, being 15.3 times that of pure SnS2 and 99.2 times that of pure ZnSn(OH)6, respectively.
[0057] (6) Cyclic stability test The SnS2 / ZnSn(OH)6 composite powder prepared in Example 3 was subjected to multiple cycles of photocatalytic degradation of NO. The results are as follows: Figure 11 As shown, after multiple cycles of use, the catalyst still maintains a high NO removal efficiency, indicating that the composite photocatalyst prepared in this invention has good photochemical stability and reusability.
[0058] (7) Performance testing of load-bearing monolithic materials A long-term photocatalytic degradation experiment of NO was conducted on the supported monolithic photocatalytic material SnS2 / ZnSn(OH)6-FC prepared in Example 5. The results are as follows: Figure 12 As shown, during the continuous long-term reaction, the supported monolithic material maintained a stable NO removal efficiency, and the catalyst did not detach significantly, indicating that the PTFE-assisted foam ceramic loading process can effectively fix the catalyst powder and meet the requirements of engineering applications.
[0059] Characterization methods including XRD, SEM, TEM, XPS, and photocurrent response confirmed that two-dimensional SnS2 nanosheets were successfully grown in situ on the surface of a three-dimensional ZnSn(OH)6 polyhedron, forming a tight interfacial contact between the two (see [link to documentation]). Figures 1 to 9 The photocatalytic NO removal performance test showed that the NO removal efficiency of the composite photocatalyst obtained in Example 3 was 15.3 times that of pure SnS2 and 99.2 times that of pure ZnSn(OH)6 (see...). Figure 10 (This is the optimal scheme in terms of overall performance among the three different proportions).
[0060] The above-described embodiments are merely preferred embodiments provided to fully illustrate the present invention, and the scope of protection of the present invention is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are all within the scope of protection of the present invention. The scope of protection of the present invention is defined by the claims.
Claims
1. A 2D / 3D coupled S-type heterojunction SnS2 / ZnSn(OH)6 photocatalyst, characterized in that: The SnS2 / ZnSn(OH)6 photocatalyst comprises a three-dimensional polyhedral ZnSn(OH)6 substrate and two-dimensional SnS2 nanosheets. The two-dimensional SnS2 nanosheets are grown in situ on the surface of the three-dimensional polyhedral ZnSn(OH)6 substrate to form a two-dimensional / three-dimensional composite structure.
2. The 2D / 3D coupled S-type heterojunction SnS2 / ZnSn(OH)6 photocatalyst according to claim 1, characterized in that: In the SnS2 / ZnSn(OH)6 photocatalyst, the molar ratio of SnS2 to ZnSn(OH)6 is 1:1 to 5:
1.
3. The 2D / 3D coupled S-type heterojunction SnS2 / ZnSn(OH)6 photocatalyst according to claim 2, characterized in that: In the SnS2 / ZnSn(OH)6 photocatalyst, the molar ratio of SnS2 to ZnSn(OH)6 is 3:
1.
4. The method for preparing the SnS2 / ZnSn(OH)6 photocatalyst according to any one of claims 1 to 3, characterized in that: Includes the following steps: (1) Preparation of three-dimensional polyhedral ZnSn(OH)6 powder; (2) Disperse the ZnSn(OH)6 powder obtained in step (1) in a solvent, add a sulfur source, and carry out a solvothermal reaction; (3) After the reaction is completed, cool, separate, wash and dry to obtain SnS2 / ZnSn(OH)6 composite powder.
5. The method for preparing the SnS2 / ZnSn(OH)6 photocatalyst according to claim 4, characterized in that: The preparation of three-dimensional polyhedral ZnSn(OH)6 powder in step (1) includes: (1a) Dissolve zinc salt and citric acid in deionized water to prepare solution A, and disperse tin salt in anhydrous ethanol to prepare solution B; (1b) Mix solution A and solution B, and add alkali solution to carry out the reaction; (1c) Add alkali solution to the system obtained in step (1b); (1d) Collect the precipitate, wash and dry it to obtain three-dimensional polyhedral ZnSn(OH)6 powder.
6. The method for preparing the SnS2 / ZnSn(OH)6 photocatalyst according to claim 5, characterized in that: The zinc salt is zinc chloride, the tin salt is tin tetrachloride pentahydrate, and the citric acid is citric acid monohydrate; the alkaline solution in steps (1b) and (1c) is sodium hydroxide solution.
7. The method for preparing the SnS2 / ZnSn(OH)6 photocatalyst according to claim 4, characterized in that: In step (2), the sulfur source is thioacetamide, the solvothermal reaction temperature is 180-220℃, and the reaction time is 10-14h.
8. A supported monolithic photocatalytic material, characterized in that: The invention comprises the SnS2 / ZnSn(OH)6 photocatalyst according to any one of claims 1 to 3, and a porous support, wherein the SnS2 / ZnSn(OH)6 photocatalyst is supported on the surface of the porous support.
9. The supported monolithic photocatalytic material according to claim 8, characterized in that: The porous carrier is alumina foam ceramic, glass fiber mesh, activated carbon, or honeycomb ceramic.
10. The application of the SnS2 / ZnSn(OH)6 photocatalyst according to any one of claims 1 to 3, or the supported monolithic photocatalytic material according to claim 8 or 9, in the photocatalytic degradation of nitrogen oxides.